Friendshoring in global production networks: State-orchestrated coupling amid geopolitical uncertainty - Linus Kalvelage; Gideon Tups (ZFW - Advances in Economic Geography, 2024)
In an era of multiple crises and geopolitical uncertainty, the need to deal with heightened risk drives states to locate strategic global production networks (GPNs) in geopolitically aligned states, a trend known as friendshoring. In this paper, we contribute to the literature on the role of geopolitics in GPNs by exploring why and how states engage in friendshoring. To this end, we distill from the literature three geopolitical imperatives that, in addition to more conventional GPN imperatives, drive strategic coupling dynamics: reducing risk exposure, (de-)weaponizing supply chains, and maintaining extraterritorial influence. States and state-linked institutions respond to these imperatives by actively 'pushing out' new inter- and extra-firm relations in GPNs which often includes previously neglected regions in the global periphery - even when regional assets require substantial transformation. To achieve this, states orchestrate efforts at extraterritorial de-risking, outward-oriented network brokering, and extraterritorial institution-building to actively alter the coupling conditions. By applying our framework to qualitative research on the Chinese soybean GPN in Tanzania and German-led green hydrogen investments in Namibia, we demonstrate how GPN friendshoring relies on both coercion or incentivization orchestrated by the state.
Keywords: 330; China; de-risking; friendshoring; geopolitics; Namibia; strategic coupling